Sinergi Kepemimpinan dan Kesadaran Masyarakat dalam Pembayaran Pajak Bumi Dan Bangunan (PBB) - Atika Purnamasari (LPPM STIE PPI, 2025)
Introduction/Main Objectives: This study aims to analyze the influence of leadership style and community awareness on compliance with Land and Building Tax (PBB) payments in Pangarengan Village, Rajeg District, Tangerang Regency. Background Problems: This study is based on the still low level of taxpayer compliance in PBB payments in rural areas, despite the government's various socialization efforts and incentives. The village head's leadership style and community awareness are thought to play an important role in encouraging tax compliance. Research Methods: The research method used is a quantitative approach with data collection techniques through questionnaires to 94 PBB taxpayer respondents in Pangarengan Village. Data analysis was conducted using SPSS 25. Finding/Results: The results showed that leadership style and community awareness have a positive and significant effect on PBB payment compliance. Conclusion: This finding indicates that the better the leadership and the higher the community awareness, the higher the regional tax compliance. The implications of this study emphasize the importance of participatory leadership and continuous education in increasing PBB revenue at the village level.